Understanding How Weed Species, Diversity And Communities Vary With Weather, Climate, Soil, Land Use And Time In Southwest Western Australia - Childs, S; Borger, Catherine; Michael, Pippa; Hashem, Abul; Renton, Michael (Asian-Pacific Weed Science Society & Weed Science Society of Indonesia, 2013)
Successful weed management depends on a sound understanding of the factors affecting the distributions of weed species and communities and how these change over time. To determine these patterns, the prevalence of weeds in fields in the south west of Western Australia was surveyed in 1997 and again in 2008 across a total of 956 sites from both surveys. Altogether 194 weed species (or groups of species within a genus) were identified. The majority of survey sites were used for cropping, and 152 weed species were identified within these cropped fields. Between 1997 and 2008, noticeable decreases in incidence (in cropped fields) were observed for Vulpia spp. (-25.3%), Aira caryophyllea (-20.5%), Bromus diandrus (-19.9%), Avena fatua (-17.6%) and Austrostipa spp. (-12.8%), with only Raphanus raphanistrum (11.3%) and Arctotheca calendula (7.1%) significantly increasing in frequency. A community analysis approach was then used to investigate potential environmental drivers of changes in community composition, including annual and seasonal temperature and rainfall over both the survey years and the preceding decades, as well as soil characteristics such as thickness, water-holding-capacity, organic carbon, bulk density and pH. This analysis showed that a wide range of edaphic and meteorological factors were significantly related to differences in weed community composition across time and space.